Association Between Preoperative US, Elastography Features and Prognostic Factors of Papillary Thyroid Cancer With BRAFV600E Mutation - Xu, Jun-Mei; Chen, Yong-Jun; Dang, Yuan-Yuan; Chen, Man (Frontiers in Endocrinology, 2020)
Purpose: To investigate the value of US and elastography for predicting prognostic factors of papillary thyroid cancer (PTC) in the positive BRAFV600E Mutation group. Materials and Methods: A total of 116 BRAFV600E Mutation patients with PTCs were enrolled in this prospective study, who were preoperatively evaluated by US, US elasticity imaging (EI), and Virtual Touch tissue imaging (VTI) and Virtual Touch tissue quantification (VTQ) of acoustic radiation force impulse (ARFI) imaging. Multivariate logistic regression analysis was performed to assess 23 independent variables for predicting prognostic factors. Diagnostic performance was evaluated with receiver operating characteristic (ROC) curve analysis. Results: Forty-two (36.2%) of 116 PTC patients with BRAFV600E Mutation had central lymph node metastasis (LNM). Nine (7.8%) and fifty-six (48.3%) had lateral LNM and extra-thyroidal extension (ETE), respectively. In multivariate logistic regression analyses, rich internal flow (odds ratio [OR]: 6.66) was the best predictor for central LNM, followed by male sex (OR: 4.22), halo sign absence (OR: 2.78) (all P<0.05). VTQ ratio (OR: 1.57) was the only predictor for lateral LNM (P=0.02). Rich internal flow (OR: 6.33) was the strongest predictor for ETE, followed by male sex (OR: 3.29), halo sign absence (OR: 2.90), and VTQ ratio (OR: 1.63) (all P<0.05). Conclusion: VTQ ratio on ARFI imaging, rich internal flow and halo sign absence on US are the predicting prognostic factors in PTC patients with BRAFV600E Mutation. The specificities were significantly increased by combining ARFI imaging and US features, which has a potential to avoid unnecessary therapeutic neck dissection in the high-risk PTC patients.